Prevalence of Canine Parvo Viral Infection in Dogs in andaround Junagadh District of Gujarat State - Sherasiya, Raisudin M; Vagh, Arshi A; Bilwal, Avinash K; Damor, Jayendra R; Parmar, Vijay L; Dodiya, Piyush G; Baria, Vinay R; Patel, Priyanshi V (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
A detailed study was conducted from October-2022 to March-2023 at the Veterinary Clinical Complex, Kamdhenu University, Junagadh,  Gujarat involving screening of 817 dogs for presence of canine parvo viral infection via Rapid test kit and PCR. The prevalence of canine  parvo virus in dogs was recorded as 4.77 % (39/817). Higher prevalence of parvovirus infection was recorded in dogs with age
Keywords: Dogs; Gastro-enteritis; Parvo virus; PCR; Prevalence; Vaccination